Comparison of Swedish and Norwegian Use of Cone-Beam Computed Tomography: a Questionnaire Study - Jerker Edén Strindberg; Caroline Hol; Gerald Torgersen; Anne Møystad; Mats Nilsson; Karin Näsström; Kristina Hellén-Halme (Stilus Optimus, 2015)
Objectives: Cone-beam computed tomography in dentistry can be used in some countries by other dentists than specialists in radiology. The frequency of buying cone-beam computed tomography to examine patients is rapidly growing, thus knowledge of how to use it is very important. The aim was to compare the outcome of an investigation on the use of cone-beam computed tomography in Sweden with a previous Norwegian study, regarding specifically technical aspects. Material and Methods: The questionnaire contained 45 questions, including 35 comparable questions to Norwegian clinics one year previous. Results were based on inter-comparison of the outcome from each of the two questionnaire studies. Results: Responses rate was 71% in Sweden. There, most of cone-beam computed tomography (CBCT) examinations performed by dental nurses, while in Norway by specialists. More than two-thirds of the CBCT units had a scout image function, regularly used in both Sweden (79%) and Norway (75%). In Sweden 4% and in Norway 41% of the respondents did not wait for the report from the radiographic specialist before initiating treatment. Conclusions: The bilateral comparison showed an overall similarity between the two countries. The survey gave explicit and important knowledge of the need for education and training of the whole team, since radiation dose to the patient could vary a lot for the same kind of radiographic examination. It is essential to establish quality assurance protocols with defined responsibilities in the team in order to maintain high diagnostic accuracy for all examinations when using cone-beam computed tomography for patient examinations.